ANALISA KEHILANGAN ENERGI PADA BOILER PABRIK KELAPA SAWIT ENERGY LOSS ANALYSIS ON THE PALM OIL MILL BOILER - Zulham Effendi; Zakwan; Amar Fauzi Nainggolan (Institut Teknologi Sawit Indonesia (ITSI), 2020)
The purpose of this paper is to calculate boiler performance by knowing energy losses during uap production.Technical analysis on the boiler is needed, as an effort to increase efficiency and know how much energy iswasted as a loss. Factors causing the greatest heat loss / heat loss in the boiler include: